Integrating the selection of PHA storing biomass and nitrogen removal via nitrite in the main wastewater treatment line. (January 2016) - Basset, N.; Katsou, E.; Frison, N.; Malamis, S.; Dosta, J.; Fatone, F.
Graphical abstract: Highlights: Selection of PHA storing biomass was integrated with N removal in municipal WWTP. N removal via nitrite was achieved using fermented biowaste as carbon source. A novel aerobic feast and anoxic famine regime was adopted for PHA selection. Denitritation driven by the stored PHA was achieved with 83 ± 13% of nitrogen removal. Oxygen requirement saving of 50% was made compared to usual PHA recovery. Abstract: A novel scheme was developed for the treatment of municipal wastewater integrating nitritation/denitritation with the selection of polyhydroxyalkanoates (PHA) storing biomass under an aerobic/anoxic, feast/famine regime. The process took place in a sequencing batch reactor (SBR) and the subsequent PHA accumulation in a batch reactor. The carbon source added during the selection and accumulation steps consisted of fermentation liquid from the organic fraction of municipal solids waste (OFMSW FL) (Period I) and OFMSW and primary sludge fermentation liquid (Period II). Selection of PHA storing biomass was successful and denitritation was driven by internally stored PHA during the famine phase. Under optimum conditions of SBR operation ammonia removal was 93%, reaching a maximum nitrite removal of 98%. The treated effluent met the nitrogen limits, while PHA-storing biomass was successfully selected. The maximum accumulation of PHA was 10.6% (wt.) since the nutrients present in the carbon source promoted bacterial growth.